Eggs and Poultry Purchase, Storage, and Preparation Practices of Consumers in Selected Asian Countries - Koppel, Kadri; Suwonsichon, Suntaree; Chitra, Uma; Lee, Jeehyun; Chambers, Edgar, IV (My University, 2014)
The objective of this study was to begin characterizing purchase, storage, handling, and preparation of poultry products and eggs by selected consumers in three Asian countries: India, Korea, and Thailand. Approximately 100 consumers in each location were recruited to participate in this study. The consumers were surveyed about eggs and poultry purchase behavior characteristics, such as temperatures and locations, storage behavior, such as storage locations in the refrigerator or freezer, preparation behavior, such as washing eggs and poultry before cooking, and handling behavior, such as using cutting boards during cooking. The results indicated differences in purchase and storage practices of raw eggs. Most Korean consumers purchased refrigerated eggs and stored the eggs in the refrigerator, while Indian and Thai consumers bought eggs that were stored at room temperature, but would refrigerate the eggs at home. Approximately half of the consumers in each country froze raw meat, poultry, or seafood. Food preparation practices showed potential for cross-contamination during cooking, such as using the same cutting board for different kinds of foods or not washing hands with soap and water. The results presented in this pilot study may lead to development of educational messages and raising consumer awareness of food safety practices in Asian countries.
Citation: Koppel, K., Suwonsichon, S., Chitra, U., Lee, J., & Chambers IV, E. (2014). Eggs and Poultry Purchase, Storage, and Preparation Practices of Consumers in Selected Asian Countries. Foods, 3(1), 110–127. https://doi.org/10.3390/foods3010110
Keywords: Consumer; Eggs; Food Safety; Poultry